Development of seedling uprooting unit for system of rice intensification - SREERAG P.M; Er. Shivaji K.P (Guide) (Tavanur 2016 DEPARTMENT OF FARM POWER MACHINERY AND ENERGY)
Development of seedling uprooting unit for system of rice intensification
Development of seedling uprooting unit for system of rice intensification